159 CHOLESTEROL CRYSTAL EMBOLIZATION: A CAUSE OF RHABDOMYOLYSIS, COMPARTMENT SYNDROME, AND GANGRENE. Issue 1 (1st January 2007) - Sarwar, S.; Al-Absi, A. I.; Wall, B. M.
Abstract : Introduction: Cholesterol crystal embolization (CCE) can involve multiple organs; however, extensive rhabdomyolysis, compartment syndrome, and gangrene leading to the need for lower extremities amputations have been rarely reported. Case Report: A 55-year-old male with a history of coronary artery disease presented with lower extremity claudication. Abdominal aortography showed severe stenosis of the right iliac and femoral arteries. He underwent percutaneous transluminal angioplasty and stenting of the right common iliac, right superficial femoral, and distal popliteal arteries. Twelve hours afterward, he developed severe bilateral lower extremity pain and soon thereafter developed extensive lower extremity livedo reticularis. Laboratory studies: serum creatinine 1.5 mg/dL, K+ 6.2 mmol/L, and CPK 48, 769 U/L, WBC count 19, 200 cmm 3 and Hct 39%. Urinalysis showed red appearance, 3+ blood without RBCs, and positive for myoglobin. The diagnosis of extensive CCE with rhabdomyolysis was made. Aggressive hydration and urinary alkalization with sodium bicarbonate-containing fluids were initiated. On day 2, he developed bilateral calf swelling with compartment pressures of 60 to 70 mm Hg, requiring bilateral lower extremity fasciotomies. With continuing hydration, serum creatinine decreased to 1.1 mg/dL and myoglobinuria gradually resolved. He eventually developed gangrene of both lower extremities, leading to bilateral below-knee amputations. Histopathology of the lower extremities showed cholesterol clefts within medium-sized arteries and arterioles in skeletal muscle, the hallmark of CCE. Discussion: CCE can be spontaneous or iatrogenic, with angiography being the most common precipitating factor. In our patient, CCE resulted in occlusion of muscular arteries, resulting in muscle necrosis, rhabdomyolysis, and compartment syndrome, ultimately resulting in lower extremity gangrene. Occlusion of skin vessels caused livedo reticularis. This case emphasizes the potential catastrophic complications of CCE, which can occur in otherwise uncomplicated vascular procedures, including endovascular stenting for peripheral vascular disease.